Rheumatoid Arthritis Patients With Circulating Extracellular Vesicles Positive for IgM Rheumatoid Factor Have Higher Disease Activity - Arntz, Onno J.; Pieters, Bartijn C. H.; Thurlings, Rogier M.; Wenink, Mark H.; van Lent, Peter L. E. M.; Koenders, Marije I.; van den Hoogen, Frank H. J.; van der Kraan, Peter M.; van de Loo, Fons A. J. (Frontiers in Immunology, 2018)
Rheumatoid arthritis (RA) is an autoimmune inflammatory disease that mainly affects synovial joints. Validated laboratory parameters for RA diagnosis are higher blood levels of rheumatoid factor IgM (IgM-RF), anti-citrullinated protein autoantibodies (ACPA), C-reactive protein (CRP) levels and erythrocyte sedimentation rate (ESR). Clinical parameters used are the number of tender (TJC) and swollen joints (SJC) and the global patient visual analogue score (VAS). To determine disease remission in patients a disease activity score (DAS28) can be calculated based on SJC, TJC, VAS and ESR (or alternatively CRP). However, subtle and better predictive changes to follow treatment responses in individual patients cannot be measured by the above mentioned parameters nor by measuring cytokine levels in blood. As extracellular vesicles (EVs) play a role in intercellular communication and carry a multitude of signals we set out to determine their value as a biomarker for disease activity. EVs were isolated from platelet-free plasma of 41 RA patients and 24 healthy controls (HC) by size exclusion chromatography (SEC). We quantified the particle and protein concentration, using NanoSight particle tracking analysis and micro-BCA respectively, and observed no differences between RA patients and HC. In plasma of 28 out of 41 RA patients IgM-RF was detectable by ELISA, and in 13 out of these 28 seropositive RA patients (RA+) IgM-RF was also detected on their isolated pEVs (RF+ pEVs). In seronegative RA patients (RA-) we did not find any RF present on pEVs. When comparing disease parameters we found no differences between RA+ and RA- patients, except for increased ESR levels in RA+ patients. However, RA+ patients with RF+ pEVs showed significant higher levels of CRP and ESR and also VAS and DAS28 were significant increased compared to RA+ patients without RF+ pEVs. This study shows for the first time the presence of IgM-RF on pEVs in a proportion of RA+ patients with a more severe disease.